Proinflammatory Effect of Endothelial Microparticles Is Mitochondria Mediated and Modulated Through MAPKAPK2 (MAPK-Activated Protein Kinase 2) Leading to Attenuation of Cardiac Hypertrophy. Issue 6 (June 2019) - Tripathi, Dipti; Biswas, Bharti; Manhas, Amit; Singh, Abhinav; Goyal, Dipika; Gaestel, Matthias; Jagavelu, Kumaravelu
Abstract : Objective—: This study investigates the functional significance of mitochondria present in endothelial microparticles (EMP) and how MK2 (MAPKAPK2 [MAPK-activated protein kinase 2]) governs EMP production and its physiological effect on cardiac hypertrophy. Approach and Results—: Flow cytometric analysis, confocal imaging, oxygen consumption rate measurement through Seahorse were used to confirm the presence of functionally active mitochondria in nontreated EMP (EMP derived from untreated control cells), lipopolysaccharide, and oligomycin treatment increased mitochondrial reactive oxygen species activity in EMP (EMP derived from cells treated with lipopolysaccharide and EMP derived from cells treated with oligomycin, respectively). The dysfunctional mitochondria contained in EMP derived from cells treated with lipopolysaccharide and EMP derived from cells treated with oligomycin induced the expression of proinflammatory mediators in the target endothelial cells leading to the augmented adhesion of human monocytic cell line on EA.hy926 cells. Multiphoton real-time imaging detected the increased adherence of EMP derived from cells treated with oligomycin at the site of carotid artery injury as compared to EMP derived from untreated control cells. MK2 regulates EMP generation during inflammation by reducing E-selectin expression and regulating the cytoskeleton rearrangement through ROCK-2 (Rho-associated coiled-coil containing protein kinase 2) pathway. MK2-deficient EMP reduced the E-selectin and ICAM-1 (intracellular adhesion molecule-1) expression on target endothelial cells leading to reduced monocyte attachment and reduced cardiac hypertrophy in mice. Conclusions—: MK2 promotes the proinflammatory effect of EMP mediated through dysfunctional mitochondria. MK2 modulates the inflammatory effect induced during cardiac hypertrophy through EMP. Abstract : Supplemental Digital Content is available in the text.